Encyclopedia of Life Sciences 2013
DOI: 10.1002/9780470015902.a0001099.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Vertebrate Appendages

Abstract: Some vertebrates can faithfully replace complex parts of their body, a feature that is more commonly observed in invertebrates. They can perform this remarkable task because of their capacity to recruit progenitor cells and activate developmental programmes that largely parallel those used during embryogenesis. Tailed amphibians (urodeles), fish and deer provide the most striking examples of regeneration of appendages in adult animals. Frogs (anurans) can regenerate their limbs only at larval stages and can pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…Skeletal regeneration is observed in other deuterostome groups: for example in cirri regeneration of amphioxus [ 56 ], and in appendage regeneration of different vertebrates (reviewed in [ 6 ]). It has even been suggested that adult bone repair and regeneration may recapitulate embryonic bone development at a molecular level [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Skeletal regeneration is observed in other deuterostome groups: for example in cirri regeneration of amphioxus [ 56 ], and in appendage regeneration of different vertebrates (reviewed in [ 6 ]). It has even been suggested that adult bone repair and regeneration may recapitulate embryonic bone development at a molecular level [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of adult organisms, this developmental process varies extensively among animals (reviewed in [ 1 ]) and also among different parts of the same organism. Some animals, such as cnidarians and flatworms, can regenerate the entire body from small fragments [ 2 – 5 ], while others can restore only some cell tissues or particular body parts, as in vertebrates (reviewed in [ 6 ]). Echinoderms are marine deuterostomes and constitute an invertebrate phylum containing five extant classes, all possessing extensive regenerative abilities in both adult and larval forms (reviewed in [ 7 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Skeletal regeneration is observed in other deuterostome groups: for example in cirri regeneration of amphioxus (Kaneto and Wada, 2011) and in appendage regeneration of different vertebrates (reviewed by Ferretti and Health, 2013). It has even been suggested that adult bone repair and regeneration may recapitulate embryonic bone development at a molecular level (Ferguson et al, 1999).…”
Section: Evolutionary Implications For Skeletogenesis Among Deuterostomesmentioning
confidence: 99%
“…We have so far discussed in detail skeletal regeneration in the mature arms of A. filiformis and highlighted some similarities with sea urchin development. Other deuterostome groups, such as vertebrates, are in some cases able to regenerate the endoskeleton of their appendages [65][66][67].…”
Section: Evolutionary Origin Of Skeletogenesis In Deuterostomesmentioning
confidence: 99%